Activity of superoxide dismutase in guinea pigs’ bronchi in late periods of experimental allergic alveolitis development and their correction with thiotriazolin - Baida, Mariana Ljubomurivna; Fyrduchco – Regeda, Mariana Mukchailivna; Regeda, Stepan Mukchailovuch (Journal of Education, Health and Sport, 2017)
The aim of work was to make biochemical investigations for detection of pro-oxidant and antioxidant systems markers in guinea pigs` bronchi before and after treatment of thiotriazolin during experimental allergic alveolitis development. Gradual elevation of conjugated dienes and malonic dialdegyde level in the bronchi was recorded on the 44th day and 54 th of experimental allergic alveolitis development in comparison with intact animals, indicating excessive accumulation of lipid peroxidation products. In the same time activity of superoxide dismutase was reduced. Oxidative stress occurs when the balance between antioxidants and reactive oxygen species(ROS) are disrupted because of either depletion of antioxidants or accumulation of ROS. Reduction of conjugated diene and malondialdehyde content and elevation of catalase activity have been reported in animals with this experimental model of disease after using of thiotriazolin. The study of oxidative stress can provide insights into etiopathogenesis and favour the discovery of new treatments.